Comparison of Digital (Two-finger) and Video Laryngoscopy Methods during Nasogastric Tube Insertion in Intubated Patients: Digital (Two-finger) and Video Laryngoscopy Methods during NGT Insertion - Nasr Isfahani, Mehdi; Nasri Nasrabadi, Elahe (Archives of Academic Emergency Medicine, 2021)
Background: Performing Nasogastric Tube (NGT) insertion is very challenging in anesthetized and intubated patients and a conclusive method has not yet been presented in this regard. Hence, the current study aimed at comparing Digital (two-finger) and Video Laryngoscopy methods during NGT insertion. Materials and Methods: The present clinical trial was performed on 76 intubated patients that were randomly divided into two groups. Groups A and B underwent Video Laryngoscopy and Digital (two-finger) methods, respectively. Then, the success rate, the number of attempts to insert NGT, duration of insertion, hemodynamic parameters, and patients’ satisfaction level were recorded and examined in this study. Results: The results of the study revealed that the duration of NGT insertion in group A with a mean of 19.07±2.07 seconds was significantly higher than that of group B with a mean of 11.53±2.16 seconds (P-value <0.001). Furthermore, the success rate was higher in group B as compared with group A (94.7% vs. 78.9%; P-value <0.05). Considering the interfering factors such as patients’ BMI, the chance of success in group B was reported to be 8.49 times higher than that of group A (P-value <0.05). Conclusion: Given the high success rate of NGT insertion and the speed of performing this process in the Digital method compared to Video Laryngoscopy method, the Digital method can be regarded as a safe and appropriate method. Hence, Digital method can be used in medical centers due to its ease of implementation, practicality, availability, and lack of need for advanced and expensive devices. However, application and integration of new methods with conventional ones can yield a more desirable output with a very high success rate.